Eosinophilic fasciitis and breast cancer: a case report highlighting recurrence signals - Vincenzo Maione; Laura Miccio; Sara Rovaris; Davide Zardo; Stefano Bighetti; Luca Bettolini; Luigi Naldi (PAGEPress Publications, 2024)
Eosinophilic Fasciitis (EF) poses a diagnostic challenge owing to its uncommon occurrence and aetiology that remains poorly understood. We report a case of a 79-year-old woman with a prolonged history of breast cancer exhibiting EF with concomitant pelvic metastases. This case underscores EF's potential as an indicator signaling a potential resurgence of cancer, highlighting its significance as a red flag of disease recurrence.